INTEGRATION OF ARTIFICIAL INTELLIGENCE IN 21ST CENTURY EDUCATION CURRICULUM - Loso Judijanto; M. Syarif; Rengga Yudha Santoso (CV. ADIBA AISHA AMIRA, 2024)
The integration of artificial intelligence (AI) in the 21st century education curriculum is an important step to prepare learners for the digital age. AI can be used to support the learning process and develop skills needed in the future. The application of AI in education brings positive impacts, especially for students, by transforming teaching methods and learning experiences. The integration of AI into the curriculum aims to build students' technological literacy and critical thinking skills. This is in line with the literacy needs of Science, Technology, Engineering, Arts, and Culture in the 21st century which includes data literacy and STEMAL (Science, Technology, Engineering, Mathematics, Arts, and Language). Understanding the influence of AI and the appropriate steps to integrate it into the curriculum is an important urgency. This is done to prepare learners for the Golden Indonesia 2045 and build relevant education in the future.